Novel Butein Derivatives Repress DDX3 Expression by Inhibiting PI3K/AKT Signaling Pathway in MCF-7 and MDA-MB-231 Cell Lines - Rampogu, Shailima; Kim, Seong Min; Shaik, Baji; Lee, Gihwan; Kim, Ju Hyun; Kim, Gon Sup; Lee, Keun Woo; Kim, Myeong Ok (Frontiers in Oncology, 2021)
Breast cancer is one of the major causes of mortalities noticed in women globally. DDX3 has emerged as potent target for several cancers including breast cancer to which currently there are no reported drugs. In order to find effective cancer therapeutics, three compounds were computationally designed tweaking the structure of natural compound butein. These compounds were synthesized and evaluated for their anticancer property in MCF-7 and MDA-MB-231 cell lines targeting DDX3. The in silico molecular docking studies have shown that the compounds have occupied the binding site of the human DDX3 target. Furthermore, to investigate the cell viability effect of 3a, 3b and 3c on cell growth, MCF-7 and MDA-MB-231 cell lines were treated with different concentrations of compounds for 24 and 48h and measured using MTT assay. The cell viability results showed that the compounds have induced a dose dependent suppression. Additionally, 3b and 3c have reduced the expression of DDX3 in MCF-7 and MDA-MD-231 cell lines. 3b or 3c treated the cell lines increased apoptotic protein expression. Both the compounds have induced the apoptotic cell death by elevated levels of cleaved PARP and cleaved caspase 3 and repression of the anti-apoptosis protein BCL-xL. Additionally, they have demonstrated the G2/M phase cell cycle arrest in both the cell lines. Additionally, 3c decreased PI3K and AKT levels. Our results shed light on the compounds anticancer ability of the butein analogues and these compounds can be employed as chemical spaces to design new prospective drug candidates. Additionally, our computational method can be adapted to design new chemical scaffolds as plausible inhibitors.